Effect of phenolic compound mixtures on the viability of listeria monocytogenes in meat model - Rodriguez Vaquero, Maria Jose (2011)
The aim of this work is to investigate the synergistic antibacterial effect of phenolic compound mixtures against Listeria monocytogenes in brain heart infusion (BHI) medium, and to select the best mixture for testing their antibacterial activity in a meat model system. In BHI medium, the most effective mixtures were those of gallic and caffeic acids, gallic and protocatechuic acids, and rutin and quercetin. At the concentration of 200 mg/L, the mixtures of gallic and protocatechuic, then gallic and caffeic acids, and quercetin and rutin reduced the number of inoculated cells. At the concentration of 100 mg/L, only the quercetin and rutin mixture produced the same synergistic effect. These combinations were selected for testing in meat. At 20 °C, 100 mg/L of gallic and protocatechuic, then gallic and caffeic acid, and rutin and quercetin mixtures decreased the growth of L. monocytogenes, as compared to the control. The inhibitory effect of gallic and protocatechuic acid mixtures increased at the concentration of 200 mg/L. The death of inoculated cells was observed in the treatment with 100 mg/L of all combinations at 4 °C. With the addition of 200 mg/L of these combinations, the lethal effect increased. Gallic and caffeic acid, and rutin and quercetin were the most effective mixtures since after 14 days of incubation no viable cells of Listeria monocytogenes were detected. The lowest decimal reduction times of 1.0 and 0.95 day were found for gallic and caffeic acid, and rutin and quercetin mixtures, respectively. These results demonstrate that phenolic compound mixtures have synergistic antilisterial effect with an important bacterial reduction in meat. Therefore, it is possible to search for strategies to combine the synergistic antimicrobial effects of phenolic compounds with their natural biological properties.